411 Mesenchymal Stem Cells for Shoulder Tendon Injury and Osteoarthritis. (28th February 2022) - Yasen, Z.; Funk, L.
Abstract: Introduction: In recent years there has been a boom in the advancements and research in mesenchymal stem cells (MSCs) injections for tissue regeneration. This has led to commercial products and early adoption of the technology. High profile cases, media and internet prominence of stem cell therapies have led to a patient demand for the treatment for numerous traumatic and degenerative musculoskeletal conditions. Aim: In this article we aim to review the evidence for mesenchymal stem cell therapy so far, focusing on its use in osteoarthritis and specifically tendon repair within the shoulder. Method: Through the database PubMed, the search included all animal models and clinical trials assessing the use of mesenchymal stem cells for treatment of osteoarthritis or rotator cuff pathology, up to the year 2018. Results: We identified 20 animal studies (95% positive findings) and 17 human studies (94% positive findings) for Osteoarthritis (OA) (399 patients assessed), however all therapy was targeted at the knee. Rotator cuff tear studies yielded 8 animal studies findings and 3 human studies (100% positive findings in both) (106 patients assessed). Conclusions: There is a reasonable body of evidence to support its use for the early stages of OA and as such phase III trials should be implicated. Evidence to support use of MSCs for rotator cuff tendon pathology is still in early stages with variable significance, but promising. More trials need to be done to assess its efficacy for injection both at the point of surgical repair and in non-surgical patients.